Diagnostic Accuracy of Ultrasonography in Retained Soft Tissue Foreign Bodies: A Systematic Review and Meta‐analysis. (25th June 2015) - Davis, Joshua; Czerniski, Byron; Au, Arthur; Adhikari, Srikar; Farrell, Isaac; Fields, J. Matthew; Jones, Alan
Abstract Objectives Open wounds with the potential for retained foreign bodies are frequently seen in the emergency department (ED). Common foreign bodies, such as wood or glass, are often missed on physical examination and conventional radiography. The increased use of ultrasonography (US) in the ED presents an opportunity to better identify retained soft tissue foreign bodies, and understanding of its test characteristics is desirable. The authors set out to determine the test characteristics of US for detection of soft tissue foreign bodies by performing a systematic review and meta‐analysis of the existing literature. Methods This was a thorough, systematic review of OVID Medline, SCOPUS, and Cochrane databases and a limited review of Directory of Open Access Journals, Google Scholar, and ClinicalTrials.gov to identify clinical studies examining the diagnostic accuracy of US in the identification of retained soft tissue foreign bodies. Studies were selected for full‐text review by two independent reviewers to determine if they met inclusion criteria. Results were pooled for test characteristics using STATA and assessed for risk of bias and applicability using the QUADAS‐2 tool. Results This systematic search strategy identified 5, 059 unique articles, and 17 articles met inclusion criteria. Pooled sensitivity and specificity were, respectively, 72% (95% confidence interval [CI] = 57% to 83%) and 92% (95% CI = 88% to 95%). Overall quality of the studies was low and interstudy heterogeneity was high (I2 = 90%, 95% CI = 80% to 100%). Conclusions Ultrasonography is highly specific and moderately sensitive in the identification of retained soft tissue foreign bodies; however, studies to date have a high degree of heterogeneity and a high risk of bias.